Comparing performance during morning vs. afternoon training sessions in intercollegiate basketball players - Heishman, A. D.; Curtis, M. A.; Saliba, E. N.; Hornett, R. J.; Malin, S. K.; Weltman, A. L. (The Journal of Strength and Conditioning Research, 2017)
Time of day is a key factor that influences the optimization of athletic performance. Intercollegiate coaches oftentimes hold early morning strength training sessions for a variety of factors including convenience. However, few studies have specifically investigated the effect of early morning vs. late afternoon strength training on performance indices of fatigue. This is athletically important because circadian and/or ultradian rhythms and alterations in sleep patterns can affect training ability. Therefore, the purpose of the present study was to examine the effects of morning vs. afternoon strength training on an acute performance index of fatigue (countermovement jump height, CMJ), player readiness (Omegawave), and self-reported sleep quantity. We hypothesized that afternoon training sessions would be associated with increased levels of performance, readiness, and self-reported sleep. A retrospective analysis was performed on data collected over the course of the preseason on 10 elite National Collegiate Athletic Association Division 1 male basketball players. All basketball-related activities were performed in the afternoon with strength and conditioning activities performed either in the morning or in the afternoon. The average values for CMJ, power output (Power), self-reported sleep quantity (sleep), and player readiness were examined. When player load and duration were matched, CMJ (58.8 ± 1.3 vs. 61.9 ± 1.6 cm, p = 0.009), Power (6,378.0 ± 131.2 vs. 6,622.1 ± 172.0 W, p = 0.009), and self-reported sleep duration (6.6 ± 0.4 vs. 7.4 ± 0.25 p = 0.016) were significantly higher with afternoon strength and conditioning training, with no differences observed in player readiness values. We conclude that performance is suppressed with morning training and is associated with a decrease in self-reported quantity of sleep.